The Study of the Proscenium Area in an Opera House - SYGULSKA, Anna; BRAWATA, Krzysztof (Archives of Acoustics, 2017)
The paper describes issues of the proscenium area shown on the example of two opera houses. The subject of the analysis was the design of the Chamber Opera House in Kalisz and the already existing building of the Opera House in Krakow. It covers the influence of the proscenium walls and forestage ceiling on the acoustic conditions in the auditorium. Another subject of the investigation was the influence of the primary proscenium, designed in the very first opera houses in Baroque. The analyses were carried out by means of two computer softwares: Ray Model and Catt Acoustic, and such parameters as sound strength (G), reverberation time (RT), early decay time (EDT), C_80 (clarity) index and center time (T_S) were calculated. The parameters were further analyzed in the auditorium for three positions of the sound source on the stage.